(untitled) (Nigerian Journal of Technology, 2018)
Microbial system that converts organic matter to energy is proposed in this paper. An attempt is made, to examine the potential of using groundnut oil mill effluent (GOME) as substrates to Microbial Fuel Cell (MFC). A methodology was developed to obtain a power density in batches by varying the feed rate of continuous flow in the MFC. The results obtained show that GOME produces higher energy per unit area compared to other mixed culture reported in scientific literatures. The minimum and maximum power densities obtained are 160 mW/m2 and 217 mW/m2 at low feed rate of (400 litre/hr) with cell potential of 625 mV and high feed rate of (420 litre /hr) with cell potential 727 mV respectively. Furthermore, the findings of this research work showed that MFC could produce higher power density at continuous flow process mode (160 mW/m2) compared to batch process (54 mW/m2). Thus, this study demonstrates the potential of generating clean energy via GOME, with by-products of carbon dioxide and water. http://dx.doi.org/10.4314/njt.v37i4.29